Herbert Croly of the New Republic : The Life and Thought of an American Progressive - Levy, David W. (Book collections on Project MUSE., 2014)
Here is the first full-length biography of Herbert Croly (1869-1930), one of the major American social thinkers of the twentieth century. David W. Levy explains the origins and impact of Croly's penetrating analysis of American life and tells the story of a career that included his founding of one of the most influential journals of the period, The New Republic, in 1914 and his writing of The Promise of American Life (1909), a landmark in the history of American ideas. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to.